Enzyme-Free Electrochemical Glucose Sensors Prepared by Dealloying Pd-Ni-P Metallic Glasses. (15th April 2014) - Zeng, Yuqiao; Xiang, Hua; Yang, Chunlei; Yang, Shengchen; Chen, Luyang; Chen, Mingwei; Inoue, Akihisa; Zhang, Xuhai; Jiang, Jianqing
Abstract : We report the formation of enzyme-free electrochemical glucose sensors by electrochemical dealloying palladium-containing Pd-Ni-P metallic glasses. When metallic glasses with different Pd contents are used as the dealloying precursor alloys, palladium-based nanoporous metals with different ligament and pore sizes can be obtained. The chemical compositions of the nanoporous metals also vary according to the different precursor compositions. All the as-obtained nanoporous metals exhibit electrochemical catalytic activity towards the oxidation of d-glucose, indicating that the nanoporous metals prepared by dealloying the Pd-Ni-P metallic glasses are promising materials for enzyme-free electrochemical glucose sensor.